2013
DOI: 10.1111/1756-185x.12172
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D on nonspecific low back pain

Abstract: Background: Nonspecific low back pain is known as one of the most common reasons for chronic low back pain (CLBP) that burdens healthcare systems with high costs. According to a hypothesis, CLBP has been associated with vitamin D 3 deficiency, the goal of this study is to evaluate the effect of vitamin D 3 administration on improvements in CLBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…Our data were in agreement with previous research, which reported that both dark skin and less pigmented skin need three to six times more sun light exposure to produce a similar ratio of vitamin D 26. In addition, other studies confirm our results that both longer duration of sunlight exposure and skin left exposed by different dressing styles were significantly associated with vitamin D levels 107110…”
Section: Discussionsupporting
confidence: 93%
“…Our data were in agreement with previous research, which reported that both dark skin and less pigmented skin need three to six times more sun light exposure to produce a similar ratio of vitamin D 26. In addition, other studies confirm our results that both longer duration of sunlight exposure and skin left exposed by different dressing styles were significantly associated with vitamin D levels 107110…”
Section: Discussionsupporting
confidence: 93%
“…Human population studies have shown that plasma levels of vitamin D are inversely associated with risk for CLBP 159. However, results from a double-blind RCT of 53 patients aged 18–40 years with nonspecific CLBP showed no significant effect of vitamin D supplementation (50,000 IU) in decreasing the pain visual analog scale score of the patients 160. Vitamin D deficiency is associated with loss of muscle strength and poor outcomes in patients with HF.…”
Section: Vitamin D and Inflammatory Diseasesmentioning
confidence: 98%
“…Los cambios medios en el dolor crónico fueron de 2.3 ± 2.6, 95% CI = 1.3-3.4 en el grupo de VD y de 3.3± 3.6, 95% CI = 0.61-2.55 en el de placebo. Concluyen que, de acuerdo con estos resultados, tanto el tratamiento con D3 como placebo mejoraron el dolor lumbar crónico y que no hubo diferencias significativas entre los grupos 42 . El anterior artículo fue criticado por varias razones: tener algunas fallas metodológicas en su diseño, en el grupo de pacientes solo un porcentaje tenían deficiencia de VD, la intensidad del dolor fue significativamente más alta en el grupo placebo que en el de VD, a pesar del tratamiento no se logró siquiera normalizar los niveles de VD y se utilizaron pruebas estadísticas inapropiadas, lo cual afecta la validez interna y externa del estudio 43 .…”
Section: Evidencia En Contraunclassified